Outcome of Laser in Situ Keratomeliusis (Lasik) in Low to High Myopia: Review of 200 Cases - P.S. Mahar, Muhammad Saeed Iqbal, Adil Salim Jafri (Pakistan Journal of Ophthalmology, 2008)
Purpose: To evaluate the visual outcome and complications of Laser in situ Keratomeliusis (LASIK) in low to high myopia (-2 to-10 Diopters). Material and Methods: A retrospective, non comparative analysis of 200 patients records was done who had Lasik procedure for myopia at Laser Vision Center, Karachi, from Oct. 2004 to Sept. 2006. Inclusive criteria were myopia between -2 to -10D and astigmatic not more than 0.5 D. Visual acuity at 1 month and 6 month and complication where recorded at six months. Results: 200 patients (400 eyes) were included in this study. 70 patients (140 eyes) were male while 130 patients (260 eyes) were female. Patients’ age ranged between 19-50 years with mean age at 34 years. All patients had myopia between -2.0DS to -10.0DS with astigmatism of no more than 0.5D. Pre operatively, 373 eyes had best spectacle corrected visual acuity (BSCVA) of 6/9 or better. At six months post LASIK, 346 eyes (92.7%) gained their vision back without correction, thirty eight (9.5%) eyes had one line decrease on Snellen’s acuity chart. No eye was recorded with decreased vision of more than a line. Dry eyes were found to be the most common problem followed by glare and myopic regression. Conclusion: Results indicated that LASIK prove it as a safe and acceptable procedure for the treatment of low to high myopia with no serious side effects.